Fostering Mental Health Literacy Among Primary School Professionals: Evaluating the Impact of an Online Training Program ‘Well@School’ - Korhonen, Joonas; Lahti, Mari; Kostadinov, Kostadin; Erjavec, Karmen; Istomina, Natalja; Ivanova, Svetla; Lagiou, Areti; Lalova, Valentina; Makutienė, Monika; Notara, Venetia; Ollikkala, Hanna; Petrova, Gergana; et al. (MDPI AG, 2025)
Mental health challenges among children and adolescents have become a pressing global concern, particularly in the wake of the COVID-19 pandemic and ongoing geopolitical instability. Addressing these issues requires innovative, cost-effective strategies, with schools serving as critical platforms for mental health promotion. This study evaluates the impact of an online training program, Well@School, designed to enhance Mental Health Literacy (MHL) among primary school professionals in Finland, Lithuania, Bulgaria, Slovenia, and Greece. Using a descriptive, cross-sectional design with pre- and post-test assessments, the study involved 223 health, education, and social care professionals. The revised Mental Health Literacy Scale (MHLS) was employed to measure changes in MHL. Results indicated a significant positive effect, with an average increase of 4 points (2.5%) in MHLS scores post-course. Bayesian analysis further confirmed this improvement, showing a high probability (99.92%) of a positive impact, with the most likely gain ranging between 3 and 5 points. The findings underscore the potential of online training programs to enhance MHL among school professionals, thereby improving their capacity to support students' mental health. This study highlights the importance of equipping primary school staff with the necessary skills to recognize and address mental health challenges, reduce stigma, and foster a supportive school environment.